Instilación ocular casual con cianoacrilato - Vega V., Miguel Ángel (Revista Hospital Clínico Universidad de Chile, 2008)
The cianocrilato is utilized in ophthalmology for the processing of small corneal drillings. We present the case of a male of 37 years that itself autoinstilo adhesive of cianoacrilato in accidental form in its left eye. In spite of the spectacularness of the situation and the diligence of the extraction of the plates, evolution of the patient was good with reepitelización corneal complete and without subsequent consequences. The bibliographical references in ophthalmology refer to the instilaciones accidental, we contribute this clinical case along with a revision of the bibliography.